Biomarkers, total organic carbon and planktonic foraminifera abundances in gravity core MSM101_44-3 from St Anns Basin, Scotian Shelf - Peter Matzerath; Henriette Marie Kolling; Kirsten Fahl; Ruediger Stein; Ralph R Schneider (PANGAEA, 2025)
Holocene sea ice and marine productivity reconstructions based on a sediment core from the northeast Scotian Shelf. The gravity core MSM101_44-3 was retieived during R/V Maria S. Merian expedition MSM101 from St. Anns Basin (45°46.651 extquotesingleN 58°31.967 extquotesingleW; 274 m water depth) in 2021 (Schneider et al., 2021). For sea-ice and productivity reconstruction of the past 10,100 years BP, biomarkers representing sea-ice algae productivity (IP25, HBI II), open-water phytoplankton productivity (dinosterol, brassicasterol), marginal ice zone (HBI III (Z), HBI III (E)), and terrigenous input (campesterol), as well as total organic carbon (TOC) and planktonic foraminifera abundances were analyzed.. The scope of the underlying study was to investigate (1) the response of sea ice to regional changes in oceanic and atmospheric conditions during the Holocene, (2) the linkage of regional Holocene sea-ice dynamics, marine productivity, and terrigenous inputs with oceanographic changes, and (3) the effects of meltwater events on sea-ice cover and primary productivity on the Scotian Shelf during the Early Holocene.